Current and future priorities for the development of optimal HIV drugs. Issue 2 (March 2019) - Vitoria, Marco; Rangaraj, Ajay; Ford, Nathan; Doherty, Meg
Abstract : Purpose of review: To summarize global efforts to accelerate access to simpler, safer and more affordable antiretroviral drugs and how this has shaped HIV treatment policy over the last decade, and outline future priorities. Several expert consultations aimed at aligning opportunities for optimization of antiretroviral drugs have been convened by WHO in partnership with academic institutions, international agencies, innovators and manufacturers. The increased access to lifelong treatment for people living with HIV also brings about new challenges in the long-term use of antiretrovirals (ARVs). Recent findings: The article describes the evolution of global research agenda on ARV optimization ascribing the characteristics of a target product profile, the importance of sequencing of first-line and second-line regimens, the role of programmatic data when looking at policy transition for new ARVs, inclusion of more subpopulations living with HIV, as well as the challenges in identifying what improvements can be made in an era where drugs are already safe, tolerable and efficacious. Summary: Within a framework of evolving treatment harmonization and simplification, future therapeutic options in development must take into consideration safety and efficacy across a range of patient populations as well the mode of administration in the context of lifelong therapy.